1992
DOI: 10.1128/jb.174.21.6800-6806.1992
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Helicobacter pylori genome map and demonstration of diversity at the genome level

Abstract: Genomic DNA from 30 strains of Helicobacter pylori was subjected to pulsed-field gel electrophoresis (PFGE) after digestion with NotI and NruI. The genome sizes of the strains ranged from 1.6 to 1.73 Mb, with an average size of 1.67 Mb. By using NotI and NruI, a circular map of H. pylori UA802 (1.7 Mb) which contained three copies of 16S and 23S rRNA genes was constructed. An unusual feature of the H. pylori genome was the separate location of at least two copies of 16S and 23S rRNA genes. Almost all strains h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
116
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 42 publications
14
116
0
Order By: Relevance
“…Some authors (Forbes e t al., 1991 ;Grothues & Tummler, 1991) have claimed that restriction fragment fingerprinting is useful for studying genetic relatedness of different strain isolates, but results with other species such as Helicobacterpylori (Taylor et al, 1992) and Bacillus c6rea.r (Carlson etal., 1992), and also our own results, prove that, at least for groups of very heterogeneous bacteria, the criteria of grouping according to restriction fragment patterns has little taxonomic value. The two B. lactofermentnm strains (and to a lesser degree the C. glzltamiczlm strain) are very closely related from the point of view of biochemical and morphological characteristics, but they represent a heterogeneous family of isolates with different genome structures.…”
Section: Closely Related Strains Show the Same Pattern Of Restrictionmentioning
confidence: 99%
“…Some authors (Forbes e t al., 1991 ;Grothues & Tummler, 1991) have claimed that restriction fragment fingerprinting is useful for studying genetic relatedness of different strain isolates, but results with other species such as Helicobacterpylori (Taylor et al, 1992) and Bacillus c6rea.r (Carlson etal., 1992), and also our own results, prove that, at least for groups of very heterogeneous bacteria, the criteria of grouping according to restriction fragment patterns has little taxonomic value. The two B. lactofermentnm strains (and to a lesser degree the C. glzltamiczlm strain) are very closely related from the point of view of biochemical and morphological characteristics, but they represent a heterogeneous family of isolates with different genome structures.…”
Section: Closely Related Strains Show the Same Pattern Of Restrictionmentioning
confidence: 99%
“…pylori has been welldocumented, although the mechanisms responsible are as yet undefined (Marshall et al, 1998). At the molecular level, the organism's genetic diversity has been shown by extensive point mutations and mosaic differences in conserved genes (Atherton et al, 1995), the presence or absence of particular loci (Xiang et aZ., 1995;Cao & Cover, 1997) and pathogenicity islands (Censini et al, 1996), and by large-scale chromosomal rearrangements (Taylor et al, 1992;Jiang et al, 1996). The identification of the trl locus in only 50% of clinical isolates tested further confirms the genetic diversity in H .…”
Section: T G G T T T C T a T T T A G T T A G T T T A C C C A T T A G mentioning
confidence: 99%
“…pylori infects up to 50 % of the human population worldwide. Tremendous genetic diversity has been reported for H. pylori and Taylor et al (1992) reported that this bacterium possesses a great deal of diversity in genomic DNA restriction profiles when analysed by pulsed-field gel electrophoresis (PFGE); the molecular and epidemiological bases for this phenomenon are not understood.…”
mentioning
confidence: 99%
“…pylori infects up to 50 % of the human population worldwide. Tremendous genetic diversity has been reported for H. pylori and Taylor et al (1992) reported that this bacterium possesses a great deal of diversity in genomic DNA restriction profiles when analysed by pulsed-field gel electrophoresis (PFGE); the molecular and epidemiological bases for this phenomenon are not understood.The aim of the study was to compare DNA profiles of H. pylori strains isolated from Lagos and Ife, Nigeria and also to determine if the isolates obtained from the antrum and corpus of the same patient were genotypically similar.Genomic DNA of 41 H. pylori strains isolated from 38 patients was prepared for PFGE, as described previously (Taylor et al, 1992). Six of the 41 isolates were from three patients, from whom biopsies were taken from both the antrum and the corpus.…”
mentioning
confidence: 99%
See 1 more Smart Citation